(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
In teaching a foreign language, certain language features (i.e. polysems and homonyms) are not introduced as issues or topics for discussion and therefore, they emerge as weeds in the discussion (Klepousniotou, 2002). When this occurs, instructors struggle to handle them differently. This article investigated the challenges of teaching Kiswahili polysems and homonyms through translation in foreign language classes. The data for this study was collected through observation and documentary review methods. Findings show that Kiswahili has a complex system of polysems than homonyms. It has been further observed that translation method alone may not be adequate in handling problematic issues such as polysems and homonyms. Since polysems and homonyms are characterized by multiple meanings, a combination of translation method and componential analysis (analysis of semantic features) works better. Lastly, instructors should teach them in context instead of treating them as isolated words and they should be introduced at the intermediate through advanced levels of foreign language proficiency.